The Potency of Cash Waqf Linked Sukuk (CWLS) on Social Development - Slamet Rusydiana, Aam; Sherrindra Avedta (SMART Insight, 2023)
This study aims to see the development of Cash Waqf Linked Sukuk (CWLS) research around the world and research path that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme CWLS which comes from the Dimensions database with a total of 60 journal articles. Then, the data was processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of CWLS research development in the world. The results of the study found that based on bibliometric keyword mapping, there are 4 clusters that can become research paths with topics related to (1)Social Development and CWLS, (2)Economic Development and CWLS, (3)Covid-19 Pandemic and CWLS and (4)MSME Development and CWLS. The author also tries to make a simulation of the impact of CWLS based on its potential, as well as the possible allocation for SDGs projects.